Análise da secagem convectiva de folhas de manjericão (Ocimum basilicum L.) - Lima, Renata de Aquino Brito (2013)
Convective drying of leaves involves heat and mass transfer in packed-beds of deformable material, since the leaves shrink significantly when the moisture is removed. Therefore, the packing structure changes over time, and the transfer properties alter as well. An additional drawback is the challenge to obtain reproducible packings, given the random nature of packing for such an irregular type of material. In this work, an experimental investigation was conducted to analyze how basil leaves (Ocimum basilicum L.) behave during drying focusing in the challenging characteristics of this particulate phase. A full characterization of the leaves as a particulate solid was conducted by measuring their dimensions, specific density, initial moisture content and equilibrium moisture content. Loose and compacted bulk densities were measured for beds of leaves under different moisture content. Results indicate that the basil leaves have a low sphericity (=0.160), a high projected area (Aproj=4.55 cm2) and density equal to 0.874 g.cm-3. Bulk density of fresh leaves was 0.089 g.cm-3 in loosely packed-beds, and 0.198 g.cm-3 in compacted packed-beds. Drying experiments were performed in a range of 30 to 60oC under different air-particle contact modes, including fixed and moving beds. Drying cells 10 cm in diameter with heights of either 1 or 12 cm (corresponding to thin-layer and deep-layer beds respectively) were tested with air flowing perpendicular to the samples. In moving beds, a rectangular chamber of dimensions 20 cm x 11 cm was used, also with air flowing perpendicular to the samples. In the conditions tested, problems were observed regarding reproducibility of data of moisture content versus time, bed shrinking, channeling and non-homogeneous drying. It was demonstrated that these problems appear due to the inherent characteristics of the leaves (low density, high ratios of surface area to volume, rough surface, etc.), and also due to their biological variability, which made it difficult to obtain packed-beds with reproducible characteristics in different assays. Homogeneous drying was obtained only for moving beds with vertical vibration, under dimensionless vibration parameter equal to 1.0 and an amplitude of vibration of 0.5 cm. The effect of the cell diameter to mean leaf size ratio (D/dm) on the bulk densities and drying rates was also investigated. For that, the size of leaves was reduced by cutting them in two parts widthways (half-sized particles), and also in four parts, width- and lengthways (quarter-sized particles), resulting in D/dm= 4.2 (whole leaves), 5.3 and 7.8 (half- and quarter-sized leaves respectively). It was observed that loose and compacted bulk densities did not vary significantly for beds of half-sized particles, but increased approximately 20% in beds of quarter-sized leaves. Regarding the drying rates, a tendency of an increase as D/dm was raised to 7.8 was observed, but the variation remained within the range of standard deviation of experimental data. Axial shrinking of the beds throughout drying was measured in deep packed-beds. The initial bed height was reduced by approximately 47% after 100 minutes of drying at 60 oC. The pressure drop through the bed decreased drastically when the leaves were dried, resulting in an increase by 141 times in the bed permeability for drying at a temperature of 60°C. The results obtained show that the packed-bed structure strongly affects the heat and mass transfer during convective drying of leaves.